Time management style and other teacher characteristics relation with pupil achievement in elementary mathematics - Libre, Lilian Fuertes (2006)
This study aimed to examine the elementary teachers' time management style and other teacher characteristics, and the their correlation to student performance and achievement in mathematics. The study used a survey-correlational research with observation guide results and achievement in mathematics. The instruments used were the Mathematics Achievement Test, a Teachers' Observation Guide, and a Survey Questionnaire. It was concluded that most of the time management styles are not significantly related to the achievement of pupils in mathematics. Drills and group activities positively contribute to student achievement in math; thus, teachers and pupils from central schools, who allot more time to drills and group activities, perform better in the achievement test than those from non-central schools.